Sensitivity of Digitaria insularis to herbicides in agricultural areas, in the Brazilian Cerrado biome - Correia, Núbia Maria; Rampazzo, Pedro Eduardo; Araújo, Lucas da Silva; Rossi, Caio Vitagliano Santi (Pesquisa Agropecuaria Brasileira, 2020)
The objective of this work was to evaluate the sensitivity of different populations of Digitaria insularis to the glyphosate, clethodim, and haloxyfop-P-methyl herbicides, in agricultural areas, and to develop infestation maps based on the responses of these populations. One hundred sixty-one populations suspected of being resistant were evaluated and compared to a susceptible population. When plants displayed three to four tillers, the populations were sprayed with glyphosate (1,000 g ha-1 a.e.), clethodim (108 g ha-1 a.i. + 0.5% mineral oil), and haloxyfop-P-methyl (62.35 g ha-1 a.i. + 0.5% mineral oil); plants without herbicide application were used as the control. The plant populations were classified as susceptible, intermediately resistant (with susceptible and resistant plants), or resistant to the tested herbicides. All populations were susceptible to clethodim; 97.5% were susceptible and 2.5% were intermediately resistant to haloxyfop-P-methyl; and 9.9% were susceptible, 21.1% intermediately resistant, and 68.9% resistant to glyphosate. Glyphosate-resistant populations are homogeneously distributed throughout the evaluated regions. There are no cases of D. insularis multiple resistance in the sampled regions; however, cross-resistance to glyphosate and haloxyfop-P-methyl was detected.